STRENGTHENING DISTRICT HEALTH MANAGEMENT IN LOW-MIDDLE INCOME COUNTRIES: REFLECTIONS AND WAY FORWARD - Maye Abu Omar (Indonesian Journal of Health Administration, 2020)
Introduction: Health systems in low-middle income countries are undergoing considerable changes in a context of ongoing health sector reforms. Districts have, therefore, been increasingly recognised as the level where health policies and health sector reforms are interpreted and implemented. At the same time, decentralisation in its different forms has become a popular reform in many countries, and this increases the importance of ensuring that districts have the organisational capacity to offer a good service.Aim: The article investigates the process, challenges and opportunities of health system development at district level in low-middle income countries.Discussion: While district strengthening is probably necessary in relation to the success of all other health reforms, it is argued that it has not been accorded the importance probably because it is not seen as glamorous. The district health management team must include both strengthening the capacity of individuals, but crucially also, improvement of systems. Many initiatives have been patchy and fail to provide a consistent national approach. The persistence of top-down approaches to health care works directly against districts being able to take charge of their own affairs.Conclusions: A shared vision of district strengthening must be achieved in order to progress with the achievement of Universal Health Coverage and Sustainable Development Goals. Keywords: district health strengthening, capacity building, low-middle income countries, universal health coverage.